Revolutionizing head and neck squamous cell carcinoma treatment with nanomedicine in the era of immunotherapy - Li, Hong-Xia; Gong, Yu-Wen; Yan, Pi-Jun; Xu, Yong; Qin, Gang; Wen, Wei-Ping; Teng, Fang-Yuan (Frontiers in Immunology, 2024)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent malignant tumor globally. Despite advancements in treatment methods, the overall survival rate remains low due to limitations such as poor targeting and low bioavailability, which result in the limited efficacy of traditional drug therapies. Nanomedicine is considered to be a promising strategy in tumor therapy, offering the potential for maximal anti-tumor effects. Nanocarriers can overcome biological barriers, enhance drug delivery efficiency to targeted sites, and minimize damage to normal tissues. Currently, various nano-carriers for drug delivery have been developed to construct new nanomedicine. This review aims to provide an overview of the current status of HNSCC treatment and the necessity of nanomedicine in improving treatment outcomes. Moreover, it delves into the research progress of nanomedicine in HNSCC treatment, with a focus on enhancing radiation sensitivity, improving the efficacy of tumor immunotherapy, effectively delivering chemotherapy drugs, and utilizing small molecule inhibitors. Finally, this article discussed the challenges and prospects of applying nanomedicine in cancer treatment.